2012
DOI: 10.1016/j.ygyno.2012.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Metformin potentiates the effects of paclitaxel in endometrial cancer cells through inhibition of cell proliferation and modulation of the mTOR pathway

Abstract: Objectives To examine the effects of combination therapy with metformin and paclitaxel in endometrial cancer cell lines. Methods ECC-1 and Ishikawa endometrial cancer cell lines were used. Cell proliferation was assessed after exposure to paclitaxel and metformin. Cell cycle progression was assessed by flow cytometry. hTERT expression was determined by real-time RT-PCR. Western immunoblotting was performed to determine the effect of metformin/paclitaxel on the mTOR pathway. Results Paclitaxel inhibited pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 53 publications
3
85
0
2
Order By: Relevance
“…A subsequent study found that metformin in combination with paclitaxel resulted in mainly G 2 arrest and decreased human telomerase reverse transcriptase mRNA expression. Metformin was demonstrated to potentiate the effects of paclitaxel in endometrial cancer cells by inhibiting cell proliferation and modulating the mTOR pathway (24). In another study, metformin was found to decrease high-fat-induced cardiac cell death by inhibiting ceramide synthesis.…”
Section: Discussionmentioning
confidence: 96%
“…A subsequent study found that metformin in combination with paclitaxel resulted in mainly G 2 arrest and decreased human telomerase reverse transcriptase mRNA expression. Metformin was demonstrated to potentiate the effects of paclitaxel in endometrial cancer cells by inhibiting cell proliferation and modulating the mTOR pathway (24). In another study, metformin was found to decrease high-fat-induced cardiac cell death by inhibiting ceramide synthesis.…”
Section: Discussionmentioning
confidence: 96%
“…As previous reports revealed, AMPK is upstream of the PI3K/AKT pathway (Hanna et al 2012). The researchers wanted to know whether AMPK is upstream of the PI3K/AKT pathway in A-ESCs.…”
Section: Ampk Activation Inhibits the Pi3k/akt Pathway In A-escsmentioning
confidence: 99%
“…odds ration (OR), 0.86; 95% CI, 0.63-1. In vitro cell system analyses have demonstrated that metformin: i) inhibits the growth of various endometrial cancer cell lines; ii) attenuates the invasion and metastasis of endometrial cancer cell lines by modifying the nuclear factor-κB, matrix metalloproteinase-2/9/Akt and Erk 1/2 pathways; and iii) enhances endometrial cancer cell chemosensitivity to cisplatin and paclitaxel by reducing glyoxalase I expression and regulating the mTOR signaling pathway (23,(50)(51)(52). At the molecular level, the fundamental activity of metformin inhibits mitochondrial oxidative phosphorylation, and may exert energy-associated stress on neoplastic cells (23).…”
Section: Metformin and Endometrial Cancermentioning
confidence: 99%